The day the world exploded : the earthshaking catastrophe at Krakatoa - Zimmerman, Dwight Jon (New York : Collins, 2007)
Juvenile literature.
Includes bibliographical references (p. 95) and index.
Keywords: Volcanoes -- Indonesia -- History -- 19th century -- Juvenile literature